Stability Analysis for Discrete Fractional Order Steady-State Heat Equation with Neumann Boundary Conditions - Dhineshbabu, R.; Selvam, A. George Maria (Journal of Applied Nonlinear Dynamics, 2026)
Boundary value problems have wide applications in science and technology. In this paper, one dimensional heat equation model together with initial and Neumann boundary conditions are presented and we compute the steady state solutions of our concerned problem. Furthermore, we discuss various kinds of Ulam stability analysis for the nonlinear discrete boundary value problem of fractional order $1